Electoral campaigns and political communication : a comparative analysis of EFF and ANC's framing of the land question and unemployment during 2019 elections - Mehale, Moraka Frans (My University, 2022)
The purpose of this study was to investigate the approach to land and unemployment as main electoral themes during 2019 elections in South Africa by the ANC and EFF. A qualitative, exploratory research was conducted to determine how these issues were articulated and approached using emotional and cognitive messages in the production of political content. This was to determine the implications of their use regarding issues of emphasis and ownership by political parties on the decision of constituencies. The hubs of data collection for this study were political street posters and Facebook advertisements. This study paid particular focus on the manners in which both parties framed the subjects of land and unemployment. Thus, thematic content analysis was used to determine the themes that emerged from the Facebook advertisements while semiotic analysis was applied on the data that emanated from street posters. The selection of the posters and Facebook political advertisements was guided by the issues the researcher intended to study which reflected on the ANC and EFF political advertisements. A total of 8 posters (N=8) were selected and analysed (4 for each party) and a total of 10 Facebook advertisements (5 for each party) were used for the generation of data in this study. A semi-structured interview was also conducted. The findings revealed that there are connections among political issues, images of politicians and the decision of voters. People vote based on these connections. The study therefore recommends that areas of content production need to be improved in the production of political advertisements, and that scholars need to improve the existing literature on political communication to educate the public (voters) about the persuasive strategies of the political parties
Thesis (M. A. (Communication Studies)) -- University of Limpopo, 2022
Keywords: ANC; EFF; Land and unemployment issues; Street posters; Social media; Political advertisements; Political images and Electorates participation; Political correctness; Land reform -- South Africa; Political correctness -- South Africa; Communication in politics; Political campaigns; Unemployment -- South Africa; Advertising, Political -- South Africa